The shape of the new : four big ideas and how they made the modern world - Montgomery, Scott L.; Chirot, Daniel (Book collections on Project MUSE., 2016)
This panoramic book tells the story of how revolutionary ideas from the Enlightenment about freedom, equality, evolution, and democracy have reverberated through modern history and shaped the world as we know it today. A testament to the enduring power of ideas, The Shape of the New offers unforgettable portraits of Adam Smith, Thomas Jefferson, Alexander Hamilton, Charles Darwin, and Karl Marx--heirs of the Enlightenment who embodied its highest ideals about progress--and shows how their thoughts, over time and in the hands of their followers and opponents, transformed the very nature of our beliefs, institutions, economies, and politics. Yet these ideas also hold contradictions. They have been used in the service of brutal systems such as slavery and colonialism, been appropriated and twisted by monsters like Stalin and Hitler, and provoked reactions against the Enlightenment's legacy by Islamic Salafists and the Christian Religious Right. The Shape of the New argues that it is impossible to understand the ideological and political conflicts of our own time without familiarizing ourselves with the history and internal tensions of these world-changing ideas. With passion and conviction, it exhorts us to recognize the central importance of these ideas as historical forces and pillars of the Western humanistic tradition. It makes the case that to read the works of the great thinkers is to gain invaluable insights into the ideas that have shaped how we think and what we believe.